NEBULIZERS: AERODYNAMIC DROPLET DIAMETER CHARACTERIZATION AND PHYSICOCHEMICAL PROPERTIES OF DRUGS TO TREAT SEVERE ACUTE RESPIRATORY SYNDROME CORONA VIRUS 2 (SARS-COV-2) - de Araújo Filho, Walter Duarte; de Araújo, Luciana Martins Pereira; de Oliveira, Anderson Silva; da Silva, Vagner Cardoso; Santos Júnior, Aníbal de Freitas (International Journal of Research -GRANTHAALAYAH, 2020)
Currently, several drugs are being used systemically to treat Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). However, few studies discuss the possibility of using the inhalation route for this treatment. Pneumatic and ultrasonic nebulizers are increasingly used due to the ease with which these media deliver drugs through an aerosol suspension to deliver drugs in a localized manner in the respiratory tract, providing greater efficiency of absorption. This study aims to characterize the droplet diameters by bands of "breathable particles" generated by nebulizers commercialized in Brazil (2 pneumatic and 1 ultrasonic), using the direct laminar incidence (DLI) technique. In addition, to discuss the use of drugs by inhalation based on the physicochemical and pharmacology properties. In the nebulization procedure, the images of the dispersed aero droplets were captured using the DLI technique. Droplet diameter distribution histograms were elaborated, emphasizing the range of droplets with diameters between 1.0 to 5.0 µm. The results attested that each nebulizer has its own characteristic of delivering the aerodynamic suspension in the nebulization process. In this study, DLI represents a viable alternative for characterization of the aero dispersed droplets, of drugs used worldwide to treat SARS-CoV-2 signs and symptoms.